2004
DOI: 10.1128/iai.72.6.3260-3266.2004
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide Protects Primary B Lymphocytes from Apoptosis by Preventing Mitochondrial Dysfunction and Bax Translocation to Mitochondria

Abstract: Mature B lymphocytes undergo apoptosis when they are cultured in the absence of survival factors. Gramnegative bacterial lipopolysaccharide (LPS) prevents this spontaneous apoptosis. This study aimed to better define the signaling pathway(s) involved in the antiapoptotic activity of this endotoxin. We report here that, in addition to its effects on spontaneous apoptosis, LPS protects B cells from apoptosis induced by the broad-spectrum protein kinase inhibitor staurosporine. LPS increased cell viability and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…5, B and C). LPS activates antiapoptotic signaling via NF-B and protects primary mouse spleen B cells from spontaneous and staurosporin-induced apoptosis (57). Therefore, the antiapoptotic activities induced by LPS seem to override the proapoptotic TGF-␤-induced signaling.…”
Section: Discussionmentioning
confidence: 99%
“…5, B and C). LPS activates antiapoptotic signaling via NF-B and protects primary mouse spleen B cells from spontaneous and staurosporin-induced apoptosis (57). Therefore, the antiapoptotic activities induced by LPS seem to override the proapoptotic TGF-␤-induced signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The balance between activation signals, apoptosis-inducing signals, and survival signals is notable in B cells. Mature B cells undergo spontaneous apoptosis in vitro, and their survival requires cytokines or antigenic stimulation (3,4). B cell activation by anti-IgM Ab induces B cell proliferation; however, BCR multimerization of surface Ig also can induce apoptosis (5,6).…”
mentioning
confidence: 99%
“…In the immune system, apoptosis plays a fundamental role in the development and homeostasis of lymphocytes and is essential in the negative selection and deletion of autoreactive cells (3,9,23). Recently, we reported that LPS protects primary B lymphocytes from both spontaneous and drug-induced apoptosis by preventing mitochondrial translocation of Bax, a proapoptotic protein of the Bcl2 family (45). It has been reported that Bax translocation could be blocked by Bcl-x L , the prosurvival protein of the Bcl2 family (13) whose expression could be enhanced by nuclear factor B (NF-B) activation (8).…”
mentioning
confidence: 99%